External Disruption and Creativity: When the West Looked Up to the East - Sgourev Stoyan V. (Journal of Organizational Sociology)
A key objective in explaining how creativity occurs and novelty is generated [may it be organized or not], is allowing for a mix of determinism and chance. One of the ways to create a disconnect between the creative act and the myriad factors bearing on it is by way of external jolts, disrupting not only routines and logics, but also structures of attention. The paper highlights the role of external disruption in novelty generation, and articulates a moderating mechanism of perceptual nature by drawing on the work of Foucault. As illustration, I discuss the “externalization” of artistic attention and the construction of counter-sites in late 19th century Western Europe by appropriating Japanese art to conceive of alternatives to academic art. I suggest that external disruptions are most consequential when they reinforce internal relational schisms.